Causes of hereditary metabolic diseases in patients presenting with developmental delay (Annals of Medical Research, 2023)
Aim: Developmental delay has many causes such as intrauterine infections, brain malformations, chromosomal anomalies, metabolic diseases. Between 0.8% and 15% of developmental delays are due to inherited metabolic diseases. Early diagnosis of these patients is very important in terms of the fact that some of them can be treated and also genetic counseling can be given to the family. In this study, it is aimed to emphasize the importance of reporting the clinical, biochemical and imaging characteristics, follow-up and treatment processes of the patients diagnosed with hereditary metabolic disease in patients with unexplained developmental delay/intellectual retardation, followed by the Metabolism 4 outpatient clinic of Başakşehir Çam and Sakura City Hospital.Materials and Methods: This retrospective study was conducted on the data obtained from the medical files of 192 patients aged 0-18 years, who were followed up with developmental delay/intellectual retardation between May 2021 and May 2022 in the metabolism 4 outpatient clinic of our tertiary care center.Results: The female/male ratio of the patients was 13/36, and the age range was between 3 months and 17 years. 34 patients were diagnosed with a hereditary metabolic disease and 15 patients with a non-metabolic genetic disease. There was consanguineous marriage in 23/32 of the patients with hereditary metabolic disease and 6/15 of the other patients. The most common Inherited metabolic disease groups are mitochondrial diseases, and lysosomal storage diseases.Conclusion: Patients can present at any age, and hereditary metabolic disease group has an important place in the etiology and has a great importance in terms of including many treatable diseases. For this reason, referral of patients who apply to outpatient clinics with developmental delay/intellectual retardation to metabolism outpatient clinics is of vital importance in terms of diagnosis, treatment, family screening and genetic counseling.